Learning Personalisation and Observed Learner's Self-Regulation Abilities - De Urraza María José; Kaminskiene Lina; Lehtinen Erno (Cherkas Global Univ Press, 2025)
The purpose of this article is to analyse the consistency of learning personalisation as a concept and the main characteristics that define it. Several studies focus the scope of analysis on the relevance of both teacher and student roles in the process of personalising learning. Key literature highlights three dominant components of teachers' personalising actions: attention to uniqueness, curriculum flexibility and mentoring. At the same time, the research done on the subject often refers to personalisation as a crucial dimension for promoting learner autonomy and self-regulation. The learning process, owned and driven by the learner, is treated as a result of managing a personal way of making decisions in the academic sphere. Therefore, this study focuses on the learner's ability to manage their own learning process and the sense of agency for personal and academic improvement. These aspects are outlined by several elements such as his or her self-awareness, the freedom of choice given to them and the sense of autonomy they enjoy in the traditional classroom environment. In this research, teachers' pedagogical activities were explored through a questionnaire to identify their commitment to different aspects of personalisation in their teaching. The students' activities indicating self-regulation were examined using the teachers' ratings. The results of a regression analysis showed that the three highlighted components of personalisation by the teachers in the classroom predicted students observed self-regulation.